The C terminus of the Alb3 membrane insertase recruits cpSRP43 to the thylakoid membrane - Falk, Sebastian; Ravaud, Stéphanie; Koch, Joachim; Sinning, Irmgard (The journal of biological chemistry, 2010)
The YidC/Oxa1/Alb3 family of membrane proteins controls the insertion and assembly of membrane proteins in bacteria, mitochondria, and chloroplasts. Here we describe the molecular mechanisms underlying the interaction of Alb3 with the chloroplast signal recognition particle (cpSRP). The Alb3 C-terminal domain (A3CT) is intrinsically disordered and recruits cpSRP to the thylakoid membrane by a coupled binding and folding mechanism. Two conserved, positively charged motifs reminiscent of chromodomain interaction motifs in histone tails are identified in A3CT that are essential for the Alb3-cpSRP43 interaction. They are absent in the C-terminal domain of Alb4, which therefore does not interact with cpSRP43. Chromodomain 2 in cpSRP43 appears as a central binding platform that can interact simultaneously with A3CT and cpSRP54. The observed negative cooperativity of the two binding events provides the first insights into cargo release at the thylakoid membrane. Taken together, our data show how Alb3 participates in cpSRP-dependent membrane targeting, and our data provide a molecular explanation why Alb4 cannot compensate for the loss of Alb3. Oxa1 and YidC utilize their positively charged, C-terminal domains for ribosome interaction in co-translational targeting. Alb3 is adapted for the chloroplast-specific Alb3-cpSRP43 interaction in post-translational targeting by extending the spectrum of chromodomain interactions.